MANAJEMEN STRATEGI DALAM MENGEMBANGKAN KEUNGGULAN DAYA SAING PERPUSTAKAAN UNIVERSITAS NEGERI MALANG - Haryono, Bambang; Sarwono, Sarwono; Cahyono, Teguh (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2021)
Human resource problems, vision and mission that are not according to needs, work programs and budgets must be immediately responded to by the leadership of the UM Library so that he has a competitive advantage in carrying out his duties and functions properly. This study aims to obtain a method of how the UM Library implements strategic management by describing and analyzing the environmental analysis process, strategy formulation, strategy implementation, and strategy evaluation carried out by library leaders in developing the competitive advantage of UM libraries. This study explores data and information based on direct interviews with UM Library leaders and documentation related to strategic management in developing the advantages of UM Libraries. At the stage of environmental analysis with structuration theory, developing multi-directional communication, resources exceeding national standards, realizing an eco campus, observing user behavior and collaborating with other organizations. The strategy formulation stage, by formulating a contextual and flexible vision and mission, making goals in line with the goals of institutions, national libraries and ministries, implementing coopetition strategies, and making institutional and non-institutional policies. UM Library Leaders in implementing the strategy by running programs both written and intended, optimizing capital and making easy and simple work procedures. At the strategy evaluation stage, the UM library leadership conducts internal, external, formal and informal evaluations.